GPS and Water Depth Measurements of the Thalweg of a Supraglacial Stream in Southwest Greenland, 2019 ... - Leidman, Sasha; Rennermalm, Asa (NSF Arctic Data Center, 2024)
Presented here are the Global Positioning System (GPS) positions of the thalweg of a supraglacial stream in Southwest Greenland. This data was collected in order to determine the water surface slope of the stream in order to calculate the frictional slope for a HEC-RAS 2D hydrological model boundary condition. A slope of 0.00143 was found based on this data. The particular stream reach is located roughly 1 kilometer (km) from the ice edge outside of Kangerlussuaq and was selected due to it being one of the largest supraglacial streams within walking distance of a road. Flows in the stream varied between 0.2 and 1.0 cubic meters per second (m3/s) daily during the observation period (July 13th, 2019 to August 10th, 2019). The data was collected with a Trimble R7 Global Navigation Satellite System (GNSS) rover attached to a 2 meter pole. Points were collected every 3.0 meters on average successively downstream for a total distance of 1.4 km. Water depths at the given location were collected simultaneously using ...